Moderate Prenatal Alcohol Exposure: Effects on Child IQ and Learning Problems at Age 7 1/2 Years. - Streissguth, Ann P.; Barr, Helen M.; Sampson, Paul D. (Alcoholism: Clinical & Experimental Research, 1990)
This longitudinal, prospective, population-based study examined the long-term effects of moderate prenatal alcohol exposure on 482 school aged children. Maternal reports of alcohol use obtained during pregnancy were significantly related to child IQ, achievement test scores, and classroom behaviors in second grade children, even after statistical adjustment for appropriate covariates. Consumption of two drinks per day or more on the average was related to a 7-point decrement in IQ in 7-year-old children even after statistically adjusting for appropriate covariates. Low paternal education and more children in the household were identified as environmental factors exacerbating the effect of prenatal alcohol exposure on child IQ. Learning problems were associated with the alcohol 'BINGE' pattern of five or more drinks on at least one occasion. This study shows that alcohol use patterns within the social drinking range can have long lasting effects on IQ and learning problems in young school aged children. These patterns should not be interpreted as biologic thresholds. It should also be noted that these are group effects of prenatal alcohol exposure, not necessarily predictable in the individual child, and that for the most part these children were functioning within the normal range of intelligence.